THE IMPACT OF WORK ENVIRONMENT, JOB MARKET FACTORS, AND FINANCIAL REWARDS ON CAREER INTEREST AS A TAX CONSULTANT - Adinda Violetta Caroline Wadu; Vinny Stephanie Hidayat (COMPETITIVE, 2025)
The purpose of this study is to examine how career interest in tax consulting is influenced by financial rewards, job market factors, and work environment. All students enrolled in Maranatha Christian University's S1 Accounting Study Program make up the study's population. Explanatory research is the methodology employed in this study. In sampling, purposeful sampling is employed. Thirty respondents were selected from the circulated questionnaire and used as research samples. SPSS was used to process the data. The T-test, or multiple linear regression analysis, is a method used to test hypotheses. The study's findings indicated that while work environment had an impact on career interest as tax consultants, financial and job market awards had little effect